Liposome nano‐formulation with cationic polar lipid DOTAP and cholesterol as a suitable pH‐responsive carrier for molecular therapeutic drug (all‐trans retinoic acid) delivery to lung cancer cells - Viswanathan Mariammal Berlin Grace; Devarajan David Wilson; Chandrasekharan Guruvayoorappan; Jesubatham Perinba Danisha; Lucia Bonati (IET Nanobiotechnology)
Abstract The molecular targeted drug ATRA demands a suitable carrier that delivers to the cancer site due to its poor bioavailability and drug resistance. ATRA, being a lipid with carboxylic acid, has been nano‐formulated as a cationic lipo‐ATRA with DOTAP:cholesterol:ATRA (5:4:1) and its pH‐responsive release, intracellular drug accumulation, and anticancer effect on human lung cancer (A549) cell line analysed. The analysis of the physicochemical characteristics of the developed lipo‐ATRA (0.8 µmol) revealed that the size of 231 ± 2.35 d.nm had a zeta potential of 6.4 ± 1.19 and an encapsulation efficiency of 93.7 ± 3.6%. The ATRA release from lipo‐ATRA in vitro was significantly (p ≤ 0.05) higher at acidic pH 6 compared to pH 7.5. The intracellular uptake of ATRA into lipo‐ATRA‐treated A549 cells was seven‐fold higher (0.007 ± 0.001 mg/ml) while only three‐fold uptake was observed in free ATRA treatment (0.003 ± 0.002 mg/ml). The lipo‐ATRA treatment caused a highly significant (p ≤ 0.001) decrease in percent cell viability at 48 h when compared with the free ATRA treatment. Overall, the results proved that the developed lipo‐ATRA has suitable physicochemical properties with enhanced ATRA release at acidic pH, while maintaining stability at physiologic pH and temperature. This resulted in an increased ATRA uptake by lung cancer cells with enhanced treatment efficiency. Hence, it is concluded that DOTAP lipo‐ATRA is a suitable carrier for ATRA delivery to solid cancer cells.